Strata + Hadoop World 2016--Singapore (O'Reilly Media, 2016)
"The 2016 Strata + Hadoop World conference in Singapore was an amazing rojak experience in the best sense of the term. It provided a wide-ranging collection of the globe's most insightful information about big data and machine learning and how these technologies are reshaping the world's businesses, institutions, and governments. This video compilation gives you a complete recording of each of the conference's 73 sessions, 8 tutorials, and 10 keynotes covering topics like big data in retail, finance, and telecommunications; real-time IoT analytics; recommendation algorithms; high-efficiency AI and ML distributed systems; ubiquitous computing; collaboration; peer analytics; Apache Beam; Apache Flink; structured streaming; and much, much more. Get this video and you'll enjoy the opportunity to learn from 122 of the world's best data engineers and data scientists working in Asia and elsewhere at data-centric companies such as Singtel, ShopBack, IHI, Lazada, Mediacorp, Qunar, Cloudera, MapR, Microsoft, Cisco, Teradata, BT Group, Google, IBM, Qubole, StarHub, SKY TV, Capgemini, and NTT Data."--Resource description page.
Title from resource description page (Safari, viewed January 26, 2017)
Keywords: Strata Conference and Hadoop World -- Singapore) -- (2016; Apache Hadoop -- Congresses; Big data -- Congresses; Data mining -- Congresses; Ubiquitous computing -- Congresses; Information science -- Congresses; Apache Hadoop; Données volumineuses; Congrès; Exploration de données (Informatique); Congrès; Informatique omniprésente; Congrès; Sciences de l'information; Congrès; Big data; Data mining; Information science; Ubiquitous computing; Conference papers and proceedings